Time Code for multifunctional 3D printhead controls - Sarah Propst; Jochen Mueller (Nature Communications)
Abstract Direct Ink Writing, an extrusion-based 3D printing technique, has attracted growing interest due to its ability to process a broad range of materials and integrate multifunctional printheads with features such as shape-changing nozzles, in-situ curing, material switching, and material mixing. Despite these advancements, incorporating auxiliary controls into Geometry Code (G-Code), the standard programming language for these printers, remains challenging. G-Code’s line-by-line execution requires auxiliary control commands to interrupt the print path motion, causing defects in the printed structure. We propose a generalizable time-based synchronization approach called Time Code (T-Code), which decouples auxiliary control from G-Code, enabling uninterrupted print path enrichment. We demonstrate the method’s effectiveness with both high-end and affordable 3D printers by fabricating functional gradients and parallelizing printhead auxiliary devices for mass customization. Our method reduces defects, enhances print speed, and minimizes the mechanical burden on 3D printers, enabling the rapid creation of complex multimaterial structures.